Review—Through-Mask Electrochemical Micromachining. Issue 16 (1st January 2018) - Baldhoff, T.; Nock, V.; Marshall, A. T.
Abstract : Through-mask electrochemical micromachining (TMEMM) is a versatile microfabrication technique, which combines anodic metal-shaping and -finishing steps in a single operation for the purpose of microstructuring a wide range of electrically conductive materials. It has been extensively utilized for the manufacture of precision-engineered components in microsystems, such as microlenses, microprobes, microactuators, microchannels and microvalves. This is because TMEMM is able to mass-produce parts; it is applicable to difficult-to-etch materials and operable under polishing conditions. This review provides an in-depth summary of the current state of TMEMM and presents key concepts relevant to its application. To this end, the interplay between the current distribution, mass-transfer effects and surface-film formation is discussed, and its effect on the machining rate, shape profile and surface finish is highlighted. Also, past incarnations of TMEMM are reviewed in terms of their masking method, substrate material, electrolyte composition and technical application. Techno-economic aspects of TMEMM are debated in relation to potential rival techniques, taking microreactor fabrication as an example for a novel area of application. This is followed by an overview of process variations and recent developments.